Differential Effects of Dietary Fats on Serum Lipids and Risks of Cardiovascular Disease and Diabetes in the Prospective Framingham Offspring Study. (29th May 2020) - Yuan, Mengjie; Pickering, R Taylor; Singer, Martha; Moore, Lynn l
Abstract: Objectives: Few studies have estimated the independent effects of butter and margarine on risk of cardiovascular disease (CVD). Our goal was to examine these effects as well as that of other fats and oils on risk of CVD and markers of cardiometabolic risk in subjects in the prospective Framingham Offspring Study. Methods: Data from 2038 adults, who were free of CVD and diabetes through exam 5 were included. Intakes of butter, margarine, mayonnaise, oils, and shortening were assessed using 3-day diet records at exams 3 and 5. Concentrations of low-density lipoproteins (LDL), high-density lipoproteins (HDL), and their particle sizes were analyzed cross-sectionally at exam 5. Subjects were followed from exam 5 to 9 for incident CVD and type 2 diabetes (T2DM) (median follow-up, 16.9 years). Cox proportional hazards models were used to estimate risk of CVD and T2DM and generalized linear models were used to evaluate effects on other cardiometabolic outcomes, while adjusting for age, sex, pack-years of smoking, BMI, physical activity, intakes of other fats, hypertension and use of lipid-lowering medication. Intake of each type of dietary fat was categorized as low, moderate, or high using sensitivity analyses. Results: Intake of >5 g/day of butter (vs. non-consumers) had no effect on CVD risk but was associated with a non-statistically significant 24% lower risk of T2DM. In men, higher butter intake was linked with larger LDL and HDL particles sizes ( P < 0.01 for both) and a lower LDL: HDL ratio ( P < 0.01). Consuming >7 g/day (vs. ≤2) of margarine was associated with a 48% (95% CI: 1.03–2.13) increased risk of CVD and a 68% (95% CI: 1.00–2.82) higher risk of T2DM in women. In men, higher margarine intake was associated with much weaker, non-statistically significant increased risks of CVD and T2DM. Finally, total intake of oils (>7 vs. ≤2 g/day) was associated with a strong reduced risk of T2DM (HR: 0.55; 95% CI: 0.36–0.85) in men but not women. There was no effect of margarine or oils on lipid particle sizes in either men or women. Conclusions: While butter intake had no adverse effect on risk of CVD in either men or women, it was beneficially associated with lipid profiles in men. In women, higher intakes of margarine but not butter were associated with increased risks of both CVD and T2DM. Finally greater oil consumption led to lower risks of T2DM in men. Funding Sources: NHLBI National Dairy Council.